Aortic Root Abscess Presenting as Pyrexia of Unknown Origin and the Importance of Echocardiography. (23rd May 2013) - Panduranga, Prashanth
Abstract : Aortic root abscess in patients with aortic endocarditis is not uncommon. Aortic root abscess may cause persistent sepsis, worsening heart failure, conduction abnormalities, fistula formation, and an increased need for surgery. We present a young patient with aortic root abscess presenting as pyrexia of unknown origin. She had acute severe aortic and mitral regurgitation which produced very soft murmurs that were easily missed. This report reiterates that a high index of suspicion is needed in suspecting valvular endocarditis as well as a comprehensive transthoracic and transesophageal echocardiographic examination to diagnose complications like aortic root abscess.